Trilateral health monitoring of seals and porpoises: What have we learned? - Gross, Stephanie; Siebert, Ursula; Kyhn, Line Anker; Thøstesen, Charlotte Bie; Alstrup, Aage Kristian Olsen; Fähndrich, Marcus; Galatius, Anders; IJsseldijk, Lonneke; Jensen, Trine Hammer; Jensen, Tim Kåre; Lakemeyer, Jan; Lehnert, Kristina; et al. (2021)
Since the first seal die-off in 1988/89, it has been recognized that investigations on the health status of marine mammals are essential to understand the development of harbour seal, grey seal and harbour porpoise populations in the Wadden Sea as part of international agreements such as the Trilateral Wadden Sea Agreement, ASCOBANS and OSPAR. Health assessment in Germany, the Netherlands and Denmark include investigations of dead marine mammals and the monitoring of life individuals. Necropsies have been conducted since 1990 according to international guidelines collecting biological and health information. Measurements of life animal’s weight, length, blubber thickness, antibody titers, blood status and chemistry data have also been conducted. The health investigations allowed identification of two epizootics caused by phocine distemper virus in 1988/89 and 2002, as well as the first Influenza A outbreak in seals in Europe in 2014. Antibody titers against these viruses are only protective for a limited number of years. Parasit target organs are lung and gastrointestinal system. Bacterial infections including zoonotic agents are frequently found affecting different organs of these marine mammals. Due to the systematic investigations of life and dead marine mammals over several decades, causes of epizootics and the zoonotic potential of marine mammals are identified and changes in the health and reproductive status, population demographics, genetics and feeding ecology assessed. The trilateral health research of marine mammals in the Wadden Sea area demonstrates the success and need of international cooperation.